Simulasi Antrian Kantor Pos Binjai Menggunakan Distribusi Pelayanan Weibull - Wisnu Satriyo Jati; Akim M.H Pardede; Novriyenni Novriyenni (Yayasan Kita Menulis, 2022)
Queues occur when an arrival cannot be matched by existing services, resulting in delays in service facilities. The waiting situation is also part of the circumstances that occur in a series of random or irregular operational activities in service facilities. The queuing system sometimes has problems, problems arise because of the large number of queues served. Queue simulation is a model that imitates a real system without having to experience the real situation and can determine the effectiveness of a system based on existing simulations. In this study, the inter-arrival time using exponential distribution and service distribution using Weibull, resulted in the average waiting time in the queue (Wq), the average waiting time for the system (Ws), the average number of customers in the queue (Lq), the average number of customers in the system(Ls), probability Server is busy(ρ)